Volcano monitoring and modelling using Distributed Acoustic Sensing (DAS) on a subglacial volcano: Grímsvötn, Iceland ... - Klaasen, Sara; Thrastarson, Solvi; Cubuk-Sabuncu, Yesim; Jónsdóttir, Kristín; Gebraad, Lars; Noe, Sebastian; Fichtner, Andreas (GFZ German Research Centre for Geosciences, 2023)
<!--!introduction!--> We present the results of an experiment with Distributed Acoustic Sensing (DAS) on Grímsvötn in Iceland, and the potential of Full Waveform Inversion with DAS. We deployed a 12 km long fibre-optic cable for one month (May 2021) on Grímsvötn, Iceland’s most active volcano, which is covered by the large Vatnajökull glacier. The cable was trenched 50 cm into the ice, following the caldera rim and ending near the central point of the caldera on top of a subglacial lake. We have discovered previously undetected levels of seismicity using an automated earthquake detection algorithm that is based on image processing techniques. We identified first arrival times with an automated cross-correlation based algorithm, developed specifically for complex and local events recorded with DAS. The first arrival times, combined with a probabilistic interpretation and the Hamiltonian Monte Carlo algorithm, yield event locations, their respective uncertainties, and effective velocities along ray ... : The 28th IUGG General Assembly (IUGG2023) (Berlin 2023) ...